JURIDICAL ANALYSIS OF THE LEGAL PROTECTION OF ADOPTED CHILDREN AGAINST DIVORCE OF ADOPTIVE PARENTS - Rizki, Rizki; Nainggolan, Zelah Fehat Nikita; Effrisna Ivana Br Sinuhaji, Ella; Unedo Hendri Keliat, Rodry (fakultas hukum universitas PGRI Semarang, 2024)
The purpose of this journal is to find out how the legal consequences of child adoption and the legal protection of an adopted child in Mahkmah Decision 1149 / Pdt. Lmg To answer the problem studied, the author uses a normative type of research and the approach used in this research is a statutory approach. Based on the results of the study that the appointment of a child who is not legalized by a court decision has legal consequences, the legal relationship between the adopted child and his adoptive parents does not occur, which means that if in the future there is a problem or dispute, each party (in this case the adoptive parents and the adopted child) cannot sue each other before the Court, so the rights and obligations of each party cannot be demanded to the Court, and several other legal consequences. For the issue of protection, the adopted child is entitled to legal status and this is evidenced by a court decision that legally states that the appointment of a child has occurred and is valid in the eyes of the law.